El espacio de las escuelas secundarias de Córdoba Capital, 2017: una caracterización multidimensional - Manuel Alejandro Giovine; Ana María Antolín Solache (Espacios en Blanco. Serie Indagaciones)
The social space of secondary schools is constructed by means of a multidimensional analysis of data and an Ascending Hierarchical Classification technique with a double potential: to show the structure of this field in one of the most important cities in Argentina and to propose an unprecedented methodology for the analysis of educational systems. A typology of six classes of schools was obtained, differentiated mainly by the management sector, with its differentiated endowment of pedagogical and technological resources, age, size of the establishments, location in the urban space and characteristics of the student body. The methodology thus reveals its potential for thinking about a field of secondary schools and comparison with other levels and other social fields, as well as articulating the results with family reproduction strategies.